2015
DOI: 10.1039/c5ra00338e
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of marine brown algal polyphenols against oxidative stressed zebrafish with high glucose

Abstract: We observed that exposure to phlorotannins, which include 6,6-bieckol, phloroeckol, dieckol and phlorofucofuroeckol isolated from an edible brown alga, Ecklonia cava, significantly inhibited high glucose–induced ROS and cell death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…Although the heart rate of embryos increased as the concentration of MRBS increased from 0.31 to 2.5 mg/ml, the heart rate significantly decreased at the sugar concentration of 5 mg/ml and only slightly increased at the sugar concentration of 10 mg/ml. Kim et al (2015) reported that phenolic compounds may affect the heartbeat of aquatic fish. For instance, they have found that phlorotannin isolated from a brown alga considerably decreased the rate heart of zebrafish embryos treated with 150 mM glucose.…”
Section: Effects Of Sugar Solutions On Heart Ratementioning
confidence: 99%
“…Although the heart rate of embryos increased as the concentration of MRBS increased from 0.31 to 2.5 mg/ml, the heart rate significantly decreased at the sugar concentration of 5 mg/ml and only slightly increased at the sugar concentration of 10 mg/ml. Kim et al (2015) reported that phenolic compounds may affect the heartbeat of aquatic fish. For instance, they have found that phlorotannin isolated from a brown alga considerably decreased the rate heart of zebrafish embryos treated with 150 mM glucose.…”
Section: Effects Of Sugar Solutions On Heart Ratementioning
confidence: 99%
“…Phlorotannins from the edible seaweed E. cava have been shown to have sedative activity by showing positive allosteric modulation of GABA A receptors (Cho et al., , ). Furthermore, they have also been shown to have protective effects against oxidative stress in zebrafish with high glucose levels (Kim et al., ). They are a potential candidates for the treatment of Alzheimer's disease (Choi, Lee, Shin, & Lee, ).…”
Section: Biologically Active Phenolics and Pigments From Seaweedsmentioning
confidence: 99%
“…Dieckol at the same dose also decreased the oxidative effects caused by high glucose, by significantly reducing heart rate, ROS, lipid peroxidation, and cell death in zebrafish (Table 1) [60]. Furthermore, high glucose levels induced the over-expression of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2), whereas 5 treatment reduced it [60].…”
Section: Dieckolmentioning
confidence: 97%
“…Reduction of heart rate (13%), ROS formation (35%), NO level (18%), lipid peroxidation (10%), and cell death (10%) in high glucose-induced oxidative stress. Reduction of over-expression of iNOS (20%) and COX-2 (15%) [60].…”
Section: Zebrafish Embryos 20 µMmentioning
confidence: 99%